Strategic Partnership Between Universities and The Private Sector to Support Entrepreneurial Project: Kemitraan Strategis antara Universitas dan Sektor Swasta untuk Mendukung Proyek Kewirausahaan - Al-Sabaawe, Younis Mohammad; Albayati, Nashwan Hamdi Hussein; Al-Obaidy, Narmeen AbdulRazzaq Saleh (Indonesian Journal of Law and Economics Review, 2025)
General Background: Universities are pivotal in fostering economic development through their role in scientific research and innovation. Specific Background: In Iraq and other developing contexts, the synergy between universities and the private sector remains underdeveloped, limiting the impact of academic research on entrepreneurial advancement. Knowledge Gap: Despite growing attention to research incubators globally, there is a lack of comprehensive models tailored to integrate them effectively within Iraqi universities. Aims: This study proposes a structured model for implementing research business incubators aimed at enhancing strategic university–industry cooperation and supporting entrepreneurial ventures. Results: The findings reveal that Iraqi universities possess the foundational capacities necessary for incubator implementation, including human capital and organizational readiness, though these elements require systematic integration and strategic planning. Novelty: The proposed model introduces a three-phase framework—principles, mechanisms, and supportive requirements—grounded in process management theory, offering a scalable roadmap adaptable to local contexts. Implications: This research informs university policymakers and private stakeholders on how to establish collaborative incubator systems that drive innovation, reduce graduate unemployment, and align research outputs with societal and economic needs. Highlight: Strategic cooperation between universities and the private sector enhances innovation and community impact. Research incubators offer a structured process to transform academic research into viable entrepreneurial ventures. Three-phase model (principles, mechanisms, support) ensures effective and sustainable implementation of incubators. Keywords: Strategic Cooperation, Research Incubators, Entrepreneurial Projects, University Partnerships, Private Sector